Characterization and Risk Analysis of Seaweed Farming Ventures in Sorsogon, Philippines - Michelle M. Bongalonta (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Seaweed farming, a crucial part of the blue economy in Sorsogon, Philippines, operates in a dynamic and frequently unpredictable environment. This environment is vulnerable to various factors that can affect its economic viability and long-term sustainability. These challenges include fluctuating market prices, environmental risks like climate change and disease outbreaks (such as the “ice-ice” disease), and operational inefficiencies. For small-scale farmers, these risks can be particularly devastating, threatening their livelihoods and hindering the sector’s growth. This study analyzed seaweed farming operations and risks using Risk Management Theory. Data from a survey of 115 farmers in Sorsogon City and Castilla, along with interviews with stakeholders, and experts, revealed a sector dominated by small-scale and medium-scale ventures, primarily cultivating Kappaphycus alvarezii through fixed-bottom long lines. While all farmers accessed government propagules, only 20% received direct financial support, highlighting a liquidity gap. Environmental hazards, particularly typhoons and “ice-ice” disease, drove yield volatility. To mitigate these risks, the study recommends Risk Avoidance through the mandatory conversion of unviable farming systems, and Risk Reduction via the distribution of climate-resilient genotypes. These findings provide a strategic roadmap for policy interventions aimed at transforming Sorsogon’s seaweed industry from a subsistence activity into a resilient commercial enterprise.